PROGRAM LENTERA SAINS BERBASIS SCIENCE EDU-PARK UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA SD ISLAM AL-IMARAH - Rahmania Amanah Putri; Indri Suci Wardhani; Muizzatul Islamiyah; Azizah Nur Jannah; Lailatul Nuraini (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2026)
Learning scientific literacy is a crucial aspect in determining the achievement of science education in schools, especially in basic education, which is a vital level of education for imparting meaningful knowledge to children. Of course, it must also be accompanied by an interactive, inspiring, fun, challenging, and motivating learning process that can motivate students to actively participate in the learning process. Students at Al-Imarah Islamic Elementary School have minimal interest and motivation in learning science. This is also caused by the lack of innovative ways of teachers in packaging the learning process that only focuses on books. These problems can be solved through the Science edu-park-based Science Lantern Program which uses a three-method approach. First, program counseling. Second, conduct training, and lastly is assistance in science and technology. In the implementation of the program, students are given a pretest and posttest to measure the increase in students' scientific abilities. In addition, questionnaires were also given to teachers and students to measure the effectiveness of the Lentera Sains program implementation. At the end of the Science edu-park-based Science Lantern program, it can be concluded that the implementation of science edu-park has proven to be effective in improving students' scientific abilities in terms of knowledge and skills. And the response from teachers and students was very good and strongly agreed if the Science Edu-park-Based Science Lantern program could be carried out in a sustainable manner.